11 year retrospective study of tubal reanastomosis by microsurgical technique - Antaratani, Ramalingappa C.; SR, Chandana Murthy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Tubal reanastomosis is a procedure to anastomose the cut ends of the fallopian tube. Laparotomy is the most frequently used microsurgical technique for this reversal, with results showing intrauterine pregnancies ranging from 50 to 80% and a rate of ectopic pregnancy less than 5% in these series. The objective of this study was to determine the pregnancy rate and live birth rate achieved through laparotomy tubal reanastomosis. Methods: Data from 152 consecutive laparotomy tubal reanastomosis procedures done between January 2004 and December 2014 were retrospectively analyzed. All procedures were performed by the same surgeon by laparotomy using microsurgical instruments. The main outcome measures were: total pregnancy rate and live birth rate. Results: Out of 152 women, who were willing for reversal operation, 4 had fimbriectomy, 8 had residual tube length <4 cm. Remaining 140 patients underwent tubal reanastomosis. 2 patients died, 2 patient’s husband died, 22 patients were lost to follow-up, and 9 are still in follow up period. Hence 105 patients were analyzed. Total pregnancy rate was 82.8% and live birth rate 73.3%. Conclusions: Tubal reanastomosis by laparotomy with microsurgical instruments results in a satisfactory pregnancy rate.